2004
DOI: 10.1158/1078-0432.ccr-04-0429
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Clustering Analysis of Tissue Microarray Immunostaining Data Identifies Prognostically Significant Groups of Breast Carcinoma

Abstract: Prognostically relevant cluster groups, based on gene expression profiles, have been recently identified for breast cancers, lung cancers, and lymphoma. Our aim was to determine whether hierarchical clustering analysis of multiple immunomarkers (protein expression profiles) improves prognostication in patients with invasive breast cancer. A cohort of 438 sequential cases of invasive breast cancer with median follow-up of 15.4 years was selected for tissue microarray construction. A total of 31 biomarkers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
145
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(158 citation statements)
references
References 31 publications
10
145
0
3
Order By: Relevance
“…In recent years, this statistical tool has been applied to analyze immunohistochemical results on Formalinfixed paraffin-embedded tissues using multiple antibodies, and has demonstrated that tumors clustered into groups that correlated to their site of origin, 23 phenotype, 24,25 biologic potential, 26 and prognosis. [27][28][29] Our goal was to identify a cluster of markers that can be used in combination in a diagnostic immunohistochemical panel for differentiating adenoid cystic carcinoma from polymorphous low-grade adenocarcinoma. In this study, 47 tumors were immunostained with primary antibodies against six proteins, and their expressions were subclassified into three categories (negative, focal, and diffuse expression), generating a dataset comprising of 846 (47 Â 6 Â 3) individual observations.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, this statistical tool has been applied to analyze immunohistochemical results on Formalinfixed paraffin-embedded tissues using multiple antibodies, and has demonstrated that tumors clustered into groups that correlated to their site of origin, 23 phenotype, 24,25 biologic potential, 26 and prognosis. [27][28][29] Our goal was to identify a cluster of markers that can be used in combination in a diagnostic immunohistochemical panel for differentiating adenoid cystic carcinoma from polymorphous low-grade adenocarcinoma. In this study, 47 tumors were immunostained with primary antibodies against six proteins, and their expressions were subclassified into three categories (negative, focal, and diffuse expression), generating a dataset comprising of 846 (47 Â 6 Â 3) individual observations.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray blocks were constructed using a manual arrayer (Beecher Instruments, Inc., Silver Springs, MD, USA) as previously described. [13][14][15] Sections (4 mm thick) were cut from the array blocks. Antigen retrieval was performed by steaming for 30 min in citrate buffer (pH 6.0).…”
Section: Tissue Microarrays and Immunostainingmentioning
confidence: 99%
“…Moreover, an alternative approach to gene expression profiling is to use established robust laboratory technology, such as immunocytochemistry on formalin fixed paraffin embedded patient tumour samples. We and others have applied protein biomarker panels, with known relevance to breast cancer, to large numbers of cases using tissue microarrays, exploring the existence and clinical significance of distinct breast cancer classes through clustering approaches [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%